The Implementation of Technique Used by Teacher to Develop Students’ Speaking Skill: A Case Study at Muhammadiyah University of Surakarta in 2023/2024 - Vina Novitasari; Endang Fauziati (South Sulawesi Education Development (SSED), 2024)
Techniques are a way to assist students to explore and increase their ability. This study aimed to describe (1) the classroom techniques used by teacher and their purposes, (2) the teacher’s role in implementing the techniques, and (3) the elements of speaking improved in implementing the techniques. This research used a case study qualitative method. The subjects are English teachers instructing third-semester speaking classes in the English Education Department at Muhammadiyah University of Surakarta in 2023/2024. The researcher used observation, interview, and documentation to collect the data. The result of the research showed that teachers used some techniques in teaching speaking, such as conversation drill, debate, role play, and presentation. Debate and conversation drill is mostly used by the English teachers in teaching and learning speaking. Teachers’ role in implementing technique in teaching speaking are as controller and tutor. Elements that need to be improved in implementing techniques in teaching speaking, namely fluency and accuracy, then grammar, vocabulary, and pronunciation. The implementation of conversation drill and debate technique as a teaching technique developed the students’ speaking performance in terms of accuracy dealing with acceptable pronunciation, correct grammar, and appropriate word choice as well as making possible chance to students to work cooperatively, brainstorm ideas, develop vocabulary, and read to support an opinion. The researcher suggests that teachers use various techniques as it encourages students in speaking